Prenatal Cerebral Dysgenesis and Cerebral Palsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1995)
The MRIs of 70 cerebral palsy patients, aged 2-16 years, performed between 1989 and 1993 at Kansai Medical University Otokoyama Hospital, were analysed to evaluate the causative roles of pre-, peri-, and postnatal events.